"On solid ground": Family and school connectedness promotes adolescents' future orientation. Issue 5 (28th August 2013) - Crespo, Carla; Jose, Paul E.; Kielpikowski, Magdalena; Pryor, Jan
ABSTRACT: The present study investigated the role of connectedness to the family and school contexts on future orientation of New Zealand adolescents. Participants were 1774 young people (51.9% female) aged between 9 and 16 years at time 1 of the study, who reported their connectedness to family and school and their perceptions of future orientation at three times of measurement one year apart. Structural equation modelling was used to test the combined role of family and school connectedness on future orientation over time. Findings supported a multiple mediation model in that adolescents' connectedness to family and school predicted more positive perceptions of future orientation both directly and indirectly via the effect of the context variables on each other.